1984
DOI: 10.1159/000284062
|View full text |Cite
|
Sign up to set email alerts
|

First Rank Symptoms and Diagnosis of Schizophrenia in Developing Countries

Abstract: Schneider’s first rank symptoms (FRS) among schizophrenics in Karachi are compared with samples from Saudi Arabia and the UK. Although the incidence of one or more FRS were very close to Saudi Arabia, the individual FRS were different, and somatic passivity was similar to the UK. It is concluded that cultural factors are more important than religious affinity in determining symptomatology. The results could be due to selection of schizophrenic patients on Western parameters. The place of FRS in developing coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
2
5
1
Order By: Relevance
“…As regards frequencies of individual FRS (table 2), our findings were consistent with the two Asian studies [18,19], but differed from the United Kingdom study [4], Passivity phe nomena and voices commenting were the most common FRS among the Saudis [18] and the Pakistanis [19], respectively. In the United Kingdom study [4], thought aliena tion (thought broadcast, insertion and with drawal) was the most frequent finding.…”
Section: Sallehsupporting
confidence: 87%
See 2 more Smart Citations
“…As regards frequencies of individual FRS (table 2), our findings were consistent with the two Asian studies [18,19], but differed from the United Kingdom study [4], Passivity phe nomena and voices commenting were the most common FRS among the Saudis [18] and the Pakistanis [19], respectively. In the United Kingdom study [4], thought aliena tion (thought broadcast, insertion and with drawal) was the most frequent finding.…”
Section: Sallehsupporting
confidence: 87%
“…Specificity of Schneider's FRS 26.7%, consistent with some earlier studies in the developing countries [4,14], but different from some others, 56% in Saudi Arabia [18] and 53% in Pakistan [19]. As regards frequencies of individual FRS (table 2), our findings were consistent with the two Asian studies [18,19], but differed from the United Kingdom study [4], Passivity phe nomena and voices commenting were the most common FRS among the Saudis [18] and the Pakistanis [19], respectively.…”
Section: Sallehsupporting
confidence: 85%
See 1 more Smart Citation
“…Of course, we also must consider a possibility that the differences among studies are influenced by ethnic vari- [28,[33][34][35] . In 1992, the WHO Ten-Country Study, which used a different definition of FRSs from Mellor's, reported the difference in the prevalence between developed and developing countries by using the same definition of schizophrenia [13] .…”
Section: Ethnic Differences In Prevalence Of Frss In Schizophreniamentioning
confidence: 99%
“…An analysis of psychiatrie symptom formation in members of three ethnic minority groups in British Columbia (Salish Indians, Russian Doukhobortsi, and Low German Mennonites) revealed that cultural factors were the most important distinguishing criteria, more so than gender or socioeconomic status (Jilek-Aall et al 1978). The pathoplastic influence of ethnic and cultural identity is also greater than the influences of geographieal proximity, historical relations, ethnolinguistie relatedness, and religious connection: recent comparative psychiatric studies show that there are significant differences in schizophrenic manifestations between Malta and Libya (Maslowski 1986), Japan and China (Fujimori et al 1987), Korea and China (Kim et al 1993), and Pakistan and Saudi Arabia (Ahmed and Naeem 1984). The International Pilot Study of Schizophrenia (IPSS) and DOSMED global research projects, carried out in international cooperation by the WHO Mental Health Division, revealed an extremely important finding for comparative cultural psychiatry: the course and out-II come of schizophrenie psychoses were clearly and uniformly better in project sites in non-Western countries than in the centers of the highly technologically developed Western countries (Jablensky et al 1994).…”
Section: Cultural Lnfluence and Psychopathologymentioning
confidence: 99%